Management of tobacco caterpillar, Spodoptera litura in Virginia tobacco with insecticide baits - Sreedhar, U; Nageswararao, K (Indian Journal of Plant Protection, 2020)
A replicated field experiment was conducted for three seasons in flue cured Virginia (FCV) tobacco (Nicotiana tabacum) cv. Kanchan for management of tobacco leaf eating caterpillar, Spodoptera litura. Baits prepared with emamectin benzoate 5 SG, Sl NPV, Bacillus thuringiensis var. kurstaki and IGRs novaluron 10 EC and lufenuron 5 EC were evaluated in comparison with chlorpyriphos 20 EC bait for management of the pest. Tobacco plants infested, mean number of leaves damaged and per cent leaf area damaged were found to be least in emamectin benzoate bait treated plots followed by novaluron and lufenuron bait treated plots. Highest cured leaf yield (1982 kg/ha) was recorded in emamectin benzoate bait treated plots followed by that in novaluron treated plots (1931 kg/ha), which was on par with that of lufenuron bait treated plots (1812 kg/ha). The net returns (` 77,878/ha) and incremental cost benefit ratio (ICBR) (1:20.47) was highest for emamectin benzoate bait treatment followed by novaluron (` 71,433/ ha and 1:14.70), chlorpyriphos (` 54,039 and 1: 14.79) and lufenuron (` 58,332 and 1:11.56) bait treatments. Data on infestation, leaf damage and yield parameters, net returns and economics showed that baits prepared with emamectin benzoate 5 SG @ 11 g a.i /ha and IGRs novaluron 10 EC @ 50 g a.i./ha and lufenuron 5 EC @ 30 g a.i./ha were quite promising and can be used in place of chlorpyriphos 20 EC @ 200 g a.i./ ha bait in FCV tobacco field crop.